Innovative activity development at technical university (Russian characteristic aspects, problems and solution) - Chmykhalo A. Yu. Aleksandr Yurievich; Vtorushin N. A. Nikolay Anatolievich; Derkach A. I. Alena; Shmakova A. Y. Alina (2017, 2017)
Title screen